Implementation of Bilinear Pairings on Reconfigurable Hardware - Nassery, Abdul Sami

Acceleration of EMTP for Distribution Networks on Data Flow Machines using the Latency Insertion Method - Amin, Omair

Boolean Difference Based Reliability Evaluation of Fault Tolerant Circuit Structures on FPGAs - Anwer, Jahanzeb; Platzner, Marco (Euromicro Conference on Digital System Design (DSD))

A novel immersive augmented reality system for prosthesis training and assessment - Boschmann, Alexander; Dosen, Strahinja; Werner, Andreas; Raies, Ali; Farina, Dario (Proc. IEEE Int. Conf. Biomed. Health Informatics (BHI))

Adaptive playouts for online learning of policies during Monte Carlo Tree Search - Graf, Tobias; Platzner, Marco (Journal Theoretical Computer Science)

Beschleunigte Simulation elektrischer Stromnetze mit GPUs - Horstmann, Jens

Optimal Generation Dispatch of Distributed Generators Considering Fair Contribution to Grid Voltage Control - Ma, Chenjie; Kaufmann, Paul; Töbermann, J.-Christian; Braun, Martin (Renewable Energy)

Operating System Support for Reconfigurable Cache - Makeswaran, Vignesh

Private/Shared Data Classification and Implementation for a Multi-Softcore Platform - Ibne Ashraf, Ishraq

Thread Shadowing: On the Effectiveness of Error Detection at the Hardware Thread Level - Meisner, Sebastian; Platzner, Marco (Reconfigurable Computing and FPGAs (ReConFig), 2016 International Conference on)

Konzeption und Implementierung einer digitalen Ansteuerung für den Betrieb einer elektrischen Sendereinheit für induktive Energieübertragung - Schmidt, Marco

Applications of Evolutionary Computation - 19th European Conference, EvoApplications - Squillero, Giovanni; Burelli, Paolo; M. Mora, Antonio; Agapitos, Alexandros; S. Bush, William; Cagnoni, Stefano; Cotta, Carlos; De Falco, Ivanoe; Della Cioppa, Antonio; Divina, Federico; Eiben, A.E.; I. Esparcia-Alcázar, Anna; et al.

RCo-Design: New Visual Environment for Reconfigurable Embedded Systems - Ghribi, Ines; Ben Abdallah, Riadh; Khalgui, Mohamed; Platzner, Marco (Proceedings of the 30th European Simulation and Modelling Conference (ESM))

New Co-design Methodology for Real-time Embedded Systems - Ghribi, Ines; Ben Abdallah, Riadh; Khalgui, Mohamed; Platzner, Marco (Proceedings of the 11th International Conference on Software Engineering and Applications (ICSOFT-EA))

Efficient Statistical Parameter Selection for Nonlinear Modeling of Process/Performance Variation - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; De Micheli, Giovanni (IEEE Transactions on Computer-Aided Design of Integrated Circuits and Systems)

Custom Memory Controller for ReconOS - Hermansen, Sven

Self-aware Computing Systems: An Engineering Approach
Taking inspiration from self-awareness in humans, this book introduces the new notion of computational self-awareness as a fundamental concept for designing and operating computing systems. The basic ability of such self-aware computing systems is to collect information about their state and progress, learning and maintaining models containing knowledge that enables them to reason about their behaviour. Self-aware computing systems will have the ability to utilise this knowledge to effectively and autonomously adapt and explain their behaviour, in changing conditions. This book addresses these fundamental concepts from an engineering perspective, aiming at developing primitives for building systems and applications. It will be of value to researchers, professionals and graduate students in computer science and engineering.

FPGA-based acceleration of high density myoelectric signal processing - Boschmann, Alexander; Agne, Andreas; Witschen, Linus Matthias; Thombansen, Georg; Kraus, Florian; Platzner, Marco (2015 International Conference on ReConFigurable Computing and FPGAs (ReConFig))
Keywords: Electromyography; Feature extraction; Delays; Hardware Pattern recognition; Prosthetics; High definition video

Using Deep Convolutional Neural Networks in Monte Carlo Tree Search - Graf, Tobias; Platzner, Marco (Computer and Games)

Monte-Carlo Simulation Balancing Revisited - Graf, Tobias; Platzner, Marco (IEEE Computational Intelligence and Games)